Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
y = mx + c
Where
y is the y of (2, -8)
x is the x of (2, -8)
m is the gradient or slope
c is the y intercept (you don’t know what it is)
Put into equation and find c
Once find c rewrite the equation with only the m and c in numbers
Eg
y = 5x + 3 (this is an example not the answer)
Hope this is helpful if you don’t understand please comment
Where
y is the y of (2, -8)
x is the x of (2, -8)
m is the gradient or slope
c is the y intercept (you don’t know what it is)
Put into equation and find c
Once find c rewrite the equation with only the m and c in numbers
Eg
y = 5x + 3 (this is an example not the answer)
Hope this is helpful if you don’t understand please comment
Answer: the student is incorrect.
Point slope form: y - y1 = m (x - x1)
Used when given one point and a slope (m)
(2, -8) and a slope of -6
y - y1 = m (x - x1)
y - (-8) = -6(x - 2)
y + 8 = -6x + 12
- 8 - 8
y = -6x + 4
Check your answer using (2, -8):
y = -6x + 4
-8 = -6(2) + 4
-8 = -12 + 4
- 8 = -8
This statement is true.
Another way to explain why they are incorrect:
y - (-8) = -6(x - 2)
y + 8 = -6x + 12 (This is where they went wrong. Two negatives next to each other when subtracting, make a positive)
y + 8 = -6x + 12
- 8 - 8
y = -6x + 4
Hope this helps!
Point slope form: y - y1 = m (x - x1)
Used when given one point and a slope (m)
(2, -8) and a slope of -6
y - y1 = m (x - x1)
y - (-8) = -6(x - 2)
y + 8 = -6x + 12
- 8 - 8
y = -6x + 4
Check your answer using (2, -8):
y = -6x + 4
-8 = -6(2) + 4
-8 = -12 + 4
- 8 = -8
This statement is true.
Another way to explain why they are incorrect:
y - (-8) = -6(x - 2)
y + 8 = -6x + 12 (This is where they went wrong. Two negatives next to each other when subtracting, make a positive)
y + 8 = -6x + 12
- 8 - 8
y = -6x + 4
Hope this helps!
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.